MemReflex: Adaptive Flashcards for Mobile Microlearning - Edge, Darren; Fitchett, Stephen; Whitney, Michael; Landay, James (MobileHCI 2012 Conference on Human Computer Interaction with Mobile Devices and Services, 2012)
Flashcard systems typically help students learn facts (e.g., definitions, names, and dates), relying on intense initial memorization with subsequent tests delayed up to days later. This approach does not exploit the short, sparse, and mobile opportunities for microlearning throughout the day, nor does it support learners who need the motivation that comes from successful study sessions. In contrast, our MemReflex system of adaptive flashcards gives fast-feedback by retesting new items in quick succession, dynamically scheduling future tests according to a model of the learner’s memory. We evaluate MemReflex across three user studies. In the first two studies, we demonstrate its effectiveness for both audio and text modalities, even while walking and distracted. In the third study of second-language vocabulary learning, we show how MemReflex enhanced learner accuracy, confidence, and perceptions of control and success. Overall, the work suggests new directions for mobile microlearning and “micro activities” in general.
Best Paper Award